RAPPROCHEMENT BETWEEN SUNNISM AND SHIISM IN INDONESIA - Asfa Widiyanto (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2021)
Throughout Islamic history, we observe enmity and conflicts between Sunnism and Shiism, nonetheless there has been also reconciliation between these sects. This article examines the opportunities and challenges of Sunni-Shia convergence in Indonesia. Such a picture will reveal a better understanding of the features of Sunni-Shia convergence in the country and their relationship with the notion of ‘Indonesian Islam’. The hostility between Shiism and Sunnism in Indonesia is triggered by misunderstandings between these sects, politicisation of Shiism, as well as geopolitical tensions in the Middle East. These constitute the challenges of Sunni-Shia convergence. One may also observe the ventures of Sunni-Shia convergence which have been undertaken by the scholars of the Nahdlatul Ulama (NU) and Muhammadiyah, and other Islamic civil society organisations. Grounding on these enterprises and the enduring elaboration of ‘Indonesian Islam’, the opportunities of and the prospects for Sunni-Shia rapprochement in the country are envisaged.